Azobenzene oxide copolymer as well as preparation method and application thereof

By synthesizing azobenzene epoxy copolymer on fiber products and combining nanotitanium dioxide, the problems of unstable UV resistance and insufficient fiber tensile strength in the prior art are solved, and efficient UV shielding and mechanical performance improvement are achieved.

CN119751747APending Publication Date: 2025-04-04YIBIN PINGSHAN TEXTILE TECH DEV CO LTD +1
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411948915.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-27
Publication Date
2025-04-04

AI Technical Summary

Technical Problem

In the prior art, the binding degree of the anti-ultraviolet functional copolymer is not high, resulting in unstable anti-ultraviolet functional, and the tensile strength and ultraviolet shielding effect of the fiber cannot be guaranteed.

Method used

Azobenzene epoxy copolymer is prepared by reacting azobenzene-containing olefin compounds with epoxy groups by olefin addition, and combined with nanotitanium dioxide to improve the UV resistance of fiber products.

Benefits of technology

It significantly improves the mechanical properties, chemical corrosion resistance and light stability of fiber products, improves the UV resistance effect, and enables fiber products to effectively block more than 70% of ultraviolet radiation and extends service life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119751747A_ABST
    Figure CN119751747A_ABST
Patent Text Reader

Abstract

The invention provides an azo benzene ring oxide copolymer as well as a preparation method and application thereof, and belongs to the technical field of synthesis and application of azo-containing ultraviolet absorbents. According to the present invention, under the action of the soft chain agent, the azobenzene-containing olefin compound and the epoxy group-containing olefin compound are subjected to the olefin addition reaction to prepare the azobenzene oxide copolymer, such that the mechanical property, the chemical corrosion resistance and the light stability of the fiber product material can be significantly improved; besides, when the anti-ultraviolet material is finished, the TiO2 nanoparticles are combined into the polymer, so that the anti-ultraviolet property is enhanced, the surface properties such as roughness are improved, and the overall interface performance of the fiber product material is facilitated. Finally, the problems that an ultraviolet absorbent in the prior art is not long in anti-ultraviolet effect, difficult to graft, easy to dissolve out and the like are solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention specifically relates to an azobenzene epoxy copolymer and a preparation method and application thereof, and belongs to the technical field of synthesis and application of azo-containing ultraviolet absorbers. Background Art

[0002] The impact of ultraviolet rays on polymer materials is mainly reflected in the fact that their energy is higher than the bond dissociation energy of the chemical bonds in the materials, resulting in photodegradation. Ultraviolet rays with a wavelength between 290 and 400nm in sunlight can penetrate the earth's atmosphere and reach the earth's surface, and the energy of this part of ultraviolet rays is sufficient to break the covalent bonds in many polymer materials. Although short-wave ultraviolet rays with a wavelength between 100 and 280nm are more destructive to materials, most of them are shielded by the atmosphere, so they have less impact on surface materials. In practical applications, fiber products are often exposed to ultraviolet rays, which affects their performance and life. In order to extend the service life of fiber product materials, it is usually necessary to improve the material's anti-ultraviolet ability by adding anti-ultraviolet agents or using other stabilization measures.

[0003] At present, the anti-ultraviolet agents involved include: benzotriazole anti-ultraviolet agents, benzophenone anti-ultraviolet agents, azobenzene anti-ultraviolet agents, etc. Among them, azobenzene and its derivatives are widely used in optical coatings and even photoresponsive liquid crystal elastomers (LCE) due to their photochromic properties. Azobenzene undergoes photoisomerization reaction under the initiation of ultraviolet light, effectively absorbs ultraviolet light energy, and reduces the degradation of the matrix material. The application of azobenzene and its derivatives in fiber products shows great potential for enhancing the fiber surface, especially in improving the resistance to ultraviolet degradation. For example, in the electrospinning process, natural protein silk core protein is mixed with photosensitive copolymers to synthesize effective azobenzene isomerization to provide ultraviolet shielding; a cross-linking agent is used to fix the photoresponsive copolymer to the silk fabric, and the azobenzene isomerization in the cross-linked copolymer coating significantly enhances the absorption capacity of ultraviolet radiation, so that the silk fabric can effectively block more than 70% of ultraviolet radiation, which is twice the shielding capacity of the original silk fabric.

[0004] However, as in the above method, when a single factor is involved, there is still a problem that the fiber cannot be completely protected from ultraviolet degradation, resulting in a certain degree of ultraviolet degradation of the fiber product.

[0005] Although the prior art "CN112030255A A method for preparing an anti-ultraviolet textile fabric" discloses an epoxy-modified anti-ultraviolet functional copolymer, it has the following shortcomings: due to the low bonding degree of the anti-ultraviolet functional copolymer, the anti-ultraviolet function is unstable. At the same time, on the one hand, it adopts melt spinning, which has high requirements on spinnability, and on the other hand, it cannot guarantee the tensile strength of the fiber, etc.

[0006] Therefore, there is a need for an azobenzene anti-ultraviolet agent that can effectively protect fiber products from ultraviolet degradation and a preparation method thereof. Summary of the invention

[0007] In order to effectively protect fiber products from ultraviolet degradation, the present invention provides an azobenzene epoxy copolymer and a preparation method and application thereof.

[0008] In the process of compounding azobenzene ultraviolet absorbers with fiber products, the inventors found that azobenzene ultraviolet absorbers cannot be stably bonded to the surface of fiber products in the form of chemical bonds, which leads to unstable anti-ultraviolet function. Therefore, the present invention prepares azobenzene epoxy copolymers by olefin addition reaction of olefin compounds containing azobenzenes and olefin compounds containing epoxy groups, which can significantly improve the mechanical properties, chemical corrosion resistance and light stability of fiber product materials; wherein, a highly efficient ultraviolet absorber with reactive groups (epoxy groups) is synthesized by a simple synthesis method; At the same time, in this synthesis method, the inventors also found that after the reaction, the olefin compounds containing azobenzene and the olefin compounds containing epoxy groups could not react completely through the olefin addition reaction, and did not meet the process requirements (low yield). Therefore, by introducing a third olefin-containing unit as a softening agent to promote the reaction, the synthesis of azobenzene-containing polyepoxy copolymers was achieved to meet actual needs.

[0009] To enhance UV absorption, additional hybrid chemical / physical strategies were employed. TiO2 is widely used as a physical UV protection additive, known for its superior light reflectivity and chemical stability. Moreover, incorporating TiO2 nanoparticles into polymers not only enhances UV resistance but also improves surface properties such as roughness, contributing to the overall interfacial properties of the fiber product material.

[0010] In order to achieve the above technical objectives, the following technical solutions are proposed: The first object of the present invention is to provide: an azobenzene epoxy copolymer, which is prepared by using an azobenzene compound containing an olefin bond and an epoxy resin containing an olefin bond as raw materials under the action of a chain softener; The azobenzene epoxy copolymer is poly 4-butyl 6-(4-((4-(ethoxycarbonyl)-phenyl)-azo)-phenyl) 2-(oxiran-2-ylmethyl) 2-methylheptane-2,4,6-tricarboxylate, and its chemical structure is as follows: ; Among them, x:y:z=2~3:1~2:2~3.

[0011] Furthermore, the chemical structural formula of the azobenzene compound containing an olefin bond is as follows: ; Among them, R1 represents alcohol, and R2 represents alkyl, hydroxyl, carboxyl or ester group.

[0012] More specifically, the azobenzene compound containing an olefin bond is ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate or 4-((4-hydroxyphenyl)azo)phenyl acrylate.

[0013] Furthermore, the chemical structural formula of the epoxy resin containing olefin bonds is as follows: ; Wherein, R3 represents an alkyl group.

[0014] More specifically, the epoxy resin containing an olefin bond is glyceryl methacrylate or glycidyl acrylate.

[0015] Furthermore, the chemical structural formula of the epoxy resin of the chain softener is as follows: ; Wherein, R4 represents an alkyl group.

[0016] More specifically, the epoxy resin containing an olefin bond is n-butyl acrylate or n-propyl acrylate.

[0017] The second object of the present invention is to provide a method for preparing an azobenzene epoxy copolymer, comprising the following steps: The azobenzene compound containing an olefin bond, the epoxy resin containing an olefin bond and the softening agent are dissolved in solvent I in a molar ratio of 1 to 3:1 to 3:1, a catalyst with a mass fraction of 2 to 5% is added, and a reflux reaction is carried out at 75 to 85° C. for 4 to 6 hours; after the reaction is completed (the system becomes viscous), drying is carried out to obtain an azobenzene epoxy copolymer; Preferably, solvent I is tetrahydrofuran, methanol or ethanol; the polymerization effect is better and more preferably, solvent I is tetrahydrofuran, which has better solubility and requires less amount, which can promote the subsequent polymerization reaction; Preferably, the catalyst is azobisisobutyronitrile, azobisisoheptylnitrile or diphenyl peroxide, which can better promote the polymerization effect.

[0018] Among them, the azobenzene compound containing an olefin bond is prepared by the following method: 1) Add ethyl 4-aminobenzoate into water and cool it to 0-5°C to obtain a mixed solution A; 2) Adding an excess amount of hydrochloric acid aqueous solution to the mixed solution A to obtain a mixed solution B; The pH is adjusted by using hydrochloric acid, and the molar ratio of hydrochloric acid to ethyl 4-aminobenzoate is 2 to 3:1; 3) Sodium nitrite aqueous solution and sodium phenol aqueous solution were added dropwise to the mixed solution B, and filtered to obtain a solid; recrystallized with anhydrous ethanol, and filtered to obtain a reddish brown solid C, i.e., ethyl (E)-4-((4-hydroxyphenyl)azo)benzoate; Wherein, before adding the sodium phenolate aqueous solution, phenol and sodium hydroxide need to be dissolved in water in advance, that is, the sodium phenolate aqueous solution is obtained by the reaction of phenol and sodium hydroxide, and the added amounts of sodium nitrite, phenol and sodium hydroxide are the same as the added amount of 4-aminobenzoic acid ethyl ester; slowly add the solution dropwise at 0-5°C for 3h; 4) Add solid C and triethylamine to tetrahydrofuran, control the molar ratio of solid C to triethylamine to be 1:1, cool to 0-5°C; then, dropwise add an equimolar ratio of acryloyl chloride solution, react at 0-5°C for 12h, and obtain a mixture D; Then, the filtrate was collected by suction filtration and rotary evaporation; anhydrous ethanol was used as a solvent, and the yellow solid E was precipitated by recrystallization, specifically ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate; The reaction process involved is as follows: The third purpose of the present invention is to propose: using the above-mentioned azobenzene epoxy copolymer to prepare an anti-ultraviolet material.

[0019] The fourth object of the present invention is to provide a method for preparing an anti-ultraviolet material, comprising the following steps: S1: Soak the fiber product (such as PBO fiber) in the pretreatment liquid and dry it to obtain the pretreatment material; S2: The pre-treated material is immersed in the anti-ultraviolet treatment liquid at a bath ratio of 1:20 to 100, and the pre-treated material is placed in an oven for high-temperature treatment, washing, and drying to obtain an anti-ultraviolet finishing material; The preparation method of the anti-ultraviolet treatment liquid comprises: dissolving the above-mentioned azobenzene epoxy copolymer in solvent II; Preferably, solvent II is ethylene dichloride, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide; S3: Immerse the anti-ultraviolet finishing material in a solution containing nano-titanium dioxide, load it at a temperature of 180-200° C., wash it, and dry it to obtain the anti-ultraviolet material.

[0020] Furthermore, the preparation method of the pretreatment liquid includes: mixing acetone and petroleum ether in a volume ratio of 1 to 3:1 to obtain a mixed solvent; and mixing the mixed solvent with anhydrous ethanol to obtain a mixed solvent. The mixed solvent can better remove the organic layer on the fiber surface, which is convenient for subsequent combination with the azobenzene epoxy copolymer.

[0021] A further method for preparing a solution containing nano titanium dioxide comprises: adding 0.4-0.6% by mass of nano titanium dioxide to solvent II, and dispersing by ultrasonication to obtain a solution; Solvent II is dichloroethane, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide.

[0022] In this technical solution, the mechanism based on includes: A new copolymer containing photoisomerized azobenzene and epoxy groups was synthesized and grafted onto plasma-treated fiber products (such as PBO fiber surfaces). This synthesis improves the UV stability of the fiber products and their interfacial compatibility with the resin matrix; subsequently, TiO2 is further dispersed in the copolymer solution and coated (immersed) on the surface of the fiber products to form fiber products-TiO2@azo-epoxy fibers. By characterizing the structure and composition of the fibers in the modified fiber products and conducting mechanical property tests, it is shown that our modification method improves the surface roughness, UV resistance, and interfacial bonding strength with epoxy resin, that is, the comprehensive strategy of using this hybrid chemical / physical coating method provides new insights and advantages for broadening the practical application of fiber products.

[0023] Furthermore, the newly synthesized azobenzene epoxy copolymer of the present invention has a unique chemical structure and is a new type of ultraviolet absorber that can be directly chemically grafted onto the fiber surface through epoxy groups, and the anti-ultraviolet effect is further improved by nano titanium dioxide; In the specific application of the azobenzene epoxy copolymer, the fiber product can be treated with the azobenzene epoxy copolymer and then loaded with nano-titanium dioxide to finally obtain an anti-ultraviolet material; or the azobenzene epoxy copolymer and nano-titanium dioxide can be simultaneously prepared into a dispersion liquid, and then the fiber is directly treated to obtain an anti-ultraviolet fiber, that is, the choice is made according to actual needs.

[0024] In the method of preparing anti-ultraviolet materials, the chemical grafting method based on olefin addition and epoxy ring opening is combined with the existing mature technology (impregnation-curing treatment) to ensure that the azobenzene epoxy copolymer is stably and efficiently grafted to the fiber surface, ultimately forming an anti-ultraviolet product.

[0025] In addition, in the preparation method of the azobenzene epoxy copolymer of the invention, ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate with better stability is preferred; and the presence of the olefin structure allows the final high-efficiency composite anti-ultraviolet agent to be grafted and cross-linked on the target product in a variety of ways to form a permanent fixation; in addition, the addition of nano-titanium dioxide further enhances the anti-ultraviolet effect; The anti-ultraviolet agent in the prior art will fall off on the surface of the fiber product during use, which will not only reduce its anti-ultraviolet effect, but also cause certain pollution to the environment. The high-efficiency composite anti-ultraviolet agent containing multiple epoxy groups in the present invention can be firmly bonded to the fiber through a chemical grafting method to achieve durable anti-ultraviolet; in addition, the epoxy group is used as a grafting medium, and after a ring-opening reaction, it can condense with the hydroxyl group on the fiber product to form an ether bond structure, thereby grafting the azobenzene group to the surface of the fiber product. The ring-opening grafting reaction of multiple epoxy groups is an important method for functionalizing polymer materials, which can significantly improve the mechanical properties, chemical corrosion resistance and light stability of the material. Therefore, in anti-ultraviolet applications, the anti-ultraviolet ability of the fiber is enhanced by ring-opening grafting the anti-ultraviolet agent of multiple epoxy groups on the surface of the plasma-modified fiber.

[0026] The beneficial technical effects brought about by adopting this technical solution are: 1. The present invention combines the advantages of azobenzene, epoxy and nano-titanium dioxide, overcomes the defects of azobenzene being unable to be chemically grafted onto fiber products, and the problems of azobenzene and nano-titanium dioxide being unable to be used together in complementation, being easy to fall off during application, and being unable to be loaded in large quantities, so that the azobenzene epoxy copolymer UV absorber can achieve high efficiency and long-lasting UV resistance without leaching. This solves the problems of UV absorbers in the prior art, such as short-lasting UV resistance, difficulty in grafting, and easy dissolution; Second, in the present invention, during the synthesis of azobenzene, it is impossible to directly chemically graft to the fiber surface, and ordinary physical coating is easy to fall off and dissolve, thereby reducing its anti-ultraviolet performance. Therefore, epoxy groups are introduced into azobenzene to make copolymers, and the molecular chain length is increased to make azobenzene absorb UV better, and the azobenzene group can be successfully chemically grafted to the fiber surface; 3. In the present invention, the azobenzene epoxy copolymer is used to treat the fiber or fabric with UV resistance, and the anti-ultraviolet agent is grafted to the fiber or fabric surface in the form of chemical bonds through the ring-opening reaction between the epoxy groups in the copolymer and the hydroxyl groups on the fiber or fabric surface at high temperature, thereby improving the stability and UV resistance of the treated fiber or fabric; 4. In the present invention, the azobenzene epoxy copolymer is used to prepare anti-ultraviolet materials, and the anti-ultraviolet performance is enhanced by combining with nano-titanium dioxide. After anti-ultraviolet testing, the obtained anti-ultraviolet fiber products have excellent strength retention rate (up to 73.7%), while the strength retention rate of the original fiber products is only 28.2%, and the anti-ultraviolet effect is obvious. BRIEF DESCRIPTION OF THE DRAWINGS

[0027] Figure 1 The synthetic route of the azobenzene epoxy copolymer in Example 4 of the present invention; Figure 2is the nuclear magnetic resonance image of ethyl (E)-4-((4-hydroxyphenyl)azo)benzoate in Example 4 of the present invention; Figure 3 is the nuclear magnetic resonance image of ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate in Example 4 of the present invention; Figure 4 is the nuclear magnetic resonance image of the azobenzene epoxy copolymer in Example 4 of the present invention; Figure 5 is a Fourier infrared spectrum of the azobenzene epoxy copolymer in Example 4 of the present invention; Figure 6 This is a schematic diagram of the process of anti-ultraviolet finishing of PBO fiber by azobenzene epoxy copolymer in Application Example 1 of the present invention; Figure 7 Scanning electron microscope images of the treated and untreated PBO fibers in Application Example 1 of the present invention (wherein, a represents PBO fibers that have not been washed with plasma; b represents PBO fibers that have been washed with plasma; c represents PBO fibers modified with azo / epoxy copolymers; d represents PBO fibers modified with azo / epoxy copolymers and coated with nano-TiO2; e represents the energy dispersive X-ray spectrum image and elemental composition of PBO fibers modified with azo / epoxy copolymers and coated with nano-TiO2; f represents the chemical composition on the surface of PBO fibers modified with azo / epoxy copolymers and coated with nano-TiO2; g represents the elemental content on the surface of PBO fibers modified with azo / epoxy copolymers and coated with nano-TiO2); Figure 8 This is the X-ray energy spectrum of the PBO fiber finished with azobenzene epoxy copolymer and nano-titanium dioxide in Application Example 1 of the present invention; Fig. 9 This is a Fourier infrared spectrum of the azobenzene epoxy copolymer and the PBO fiber finished with nano-titanium dioxide in Application Example 1 of the present invention; Fig.10 Schematic diagram of the anti-ultraviolet performance of the PBO fiber in Application Example 1 of the present invention, the PBO fiber treated with azobenzene epoxy copolymer, and the PBO fiber treated with azobenzene epoxy copolymer-nano titanium dioxide (change in tensile strength with increasing ultraviolet aging time); Fig.11 Schematic diagram of the anti-ultraviolet performance of the PBO fiber in Application Example 1 of the present invention, the PBO fiber treated with an azobenzene epoxy copolymer, and the PBO fiber treated with an azobenzene epoxy copolymer-nano-titanium dioxide (change in the tensile strength retention rate with increasing ultraviolet aging time); Fig.12The scanning electron microscope images of the treated and untreated PBO fibers in Application Example 1 of the present invention after 288 hours of ultraviolet irradiation aging treatment (wherein, a represents the PBO fiber washed by plasma; b represents the PBO fiber modified by azo / epoxy copolymer; c represents the PBO fiber modified by azo / epoxy copolymer and coated with nano-TiO2); Fig.13 Schematic diagram of the interfacial bonding performance between the treated and untreated PBO fibers and epoxy resin in Application Example 1 of the present invention (wherein, a represents the interfacial shear strength between the plasma-washed PBO fiber, the azo / epoxy copolymer-modified PBO fiber, and the azo / epoxy copolymer-modified and nano-TiO2-coated PBO fiber and epoxy resin; b represents the pull-out image of the plasma-washed PBO fiber, and there is no residue on the fiber surface after pulling out; c represents the pull-out image of the azo / epoxy copolymer-modified PBO fiber, and some resin residue is visible on the fiber surface after a single fiber is pulled out; d represents the pull-out image of the PBO fiber modified with the azo / epoxy copolymer and nano-titanium dioxide coating, and a significant amount of bonding epoxy resin is pulled out together with the fiber during pulling out). DETAILED DESCRIPTION

[0028] The following is a clear and complete description of the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0029] Example 1 This embodiment provides: an azobenzene epoxy copolymer, prepared from ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate and glyceryl methacrylate as raw materials, under the action of a chain softening agent, n-butyl acrylate; The azobenzene epoxy copolymer is poly 4-butyl 6-(4-((4-(ethoxycarbonyl)-phenyl)-azo)-phenyl) 2-(oxiran-2-ylmethyl) 2-methylheptane-2,4,6-tricarboxylate, and its chemical structure is as follows: ; Among them, x:y:z=2:1:2 Example 2 This embodiment provides: a method for preparing an azobenzene epoxy copolymer, comprising the following steps: Ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate, glyceryl methacrylate and n-butyl acrylate are dissolved in tetrahydrofuran solvent at a molar ratio of 2:2:1, 3% by mass of azobisisobutyronitrile as a catalyst is added, and the mixture is refluxed at 80°C for 5 hours. After the reaction is completed (the system becomes viscous), the mixture is dried to obtain an azobenzene epoxy copolymer.

[0030] Wherein, ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate is prepared by the following method: 1) Add ethyl 4-aminobenzoate into water and cool it to 0-5°C to obtain a mixed solution A; 2) adding an excess amount of aqueous hydrochloric acid to the mixed solution A to obtain a mixed solution B; Hydrochloric acid is used to adjust pH, preferably, the molar ratio of hydrochloric acid to ethyl 4-aminobenzoate is 2-3:1; 3) Sodium nitrite aqueous solution and sodium phenolate aqueous solution are added dropwise to the mixed solution B, the solid is filtered out and recrystallized with anhydrous ethanol, and a reddish brown solid C is obtained by suction filtration, which is ethyl (E)-4-((4-hydroxyphenyl)azo)benzoate; Wherein, before adding the sodium phenolate aqueous solution, phenol and sodium hydroxide need to be dissolved in water in advance, that is, the sodium phenolate aqueous solution is obtained by the reaction of phenol and sodium hydroxide, and the added amounts of sodium nitrite, phenol and sodium hydroxide are the same as the added amount of ethyl 4-aminobenzoate (that is, the molar ratio of ethyl 4-aminobenzoate, sodium nitrite, phenol and sodium hydroxide is 1:1:1:1); slowly add dropwise at 0-5°C for 3h; 4) Add solid C and triethylamine to tetrahydrofuran, control the molar ratio of solid C to triethylamine to be 1:1, cool to 0-5°C, then dropwise add an equimolar ratio of acryloyl chloride solution, react for 12 hours, and obtain a mixture D; Then, the filtrate was collected by suction filtration and rotary evaporation; anhydrous ethanol was used as a solvent, and the yellow solid E was precipitated by recrystallization, which was ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate; The reaction process involved is as follows: ; The limitation of the above preparation steps and control conditions can further improve the stability and sustainability of the preparation method, while reducing costs, increasing product yield, and so on.

[0031] Example 3 This embodiment takes the production of anti-ultraviolet material as an example, and applies azobenzene epoxy copolymer to the preparation of anti-ultraviolet material.

[0032] Wherein, the preparation method of the anti-ultraviolet material comprises: (1) Soaking the fiber product-PBO fiber in a pretreatment solution and drying it to obtain a pretreated material; (2) With the bath ratio of the pre-treated material to the anti-ultraviolet treatment liquid being 1:80, the pre-treated material is immersed in the anti-ultraviolet treatment liquid, placed in an oven for high-temperature treatment, washed, and dried to obtain an anti-ultraviolet finishing material; The preparation method of the anti-ultraviolet treatment liquid comprises: dissolving an azobenzene epoxy copolymer in ethylene dichloride; (3) Immersing the anti-ultraviolet finishing material in a solution containing nano-titanium dioxide, loading, washing, and drying to obtain the anti-ultraviolet material.

[0033] Example 4 This embodiment provides a method for preparing an azobenzene epoxy copolymer, such as Figure 1 As shown, the specific steps include: 1. Add ethyl 4-aminobenzoate into deionized water, stir the solution with a stirring paddle to dissolve as much as possible, and cool it in a water bath to 0-5°C to obtain a mixed solution A; 2. Adding an excess amount of hydrochloric acid aqueous solution to the mixed solution A to adjust the solution to an acidic condition to obtain a mixed solution B; 3. Slowly add sodium nitrite aqueous solution to the mixed solution B under cold bath conditions, react for half an hour after the addition, then add phenol and sodium hydroxide aqueous solution to the solution, continue to react in the cold bath for 2 hours after the addition, filter to obtain a solid, dry it, recrystallize it with anhydrous ethanol, filter it, and dry it to obtain a reddish brown solid C, which is ethyl (E)-4-((4-hydroxyphenyl)azo)benzoate (such as Figure 2 shown); 4. Add solid C and triethylamine to tetrahydrofuran, control the molar ratio of solid C to triethylamine to be 1:1, cool to 0-5°C, then dropwise add acryloyl chloride solution in an equal molar ratio, react to obtain a mixture D; then, filter and collect the filtrate, and perform rotary evaporation; use anhydrous ethanol as solvent, and recrystallize to precipitate a yellow solid E, which is ethyl (E)-4-((4-(acryloyloxy)phenyl)azo)benzoate (such as Figure 3 shown); 5. Dissolve solid E, glyceryl methacrylate and n-butyl acrylate in tetrahydrofuran, add 2-5% by mass of azobisisobutyronitrile, react, and when the system becomes viscous, take out and put into an oven to obtain a reddish brown solid F, which is an azobenzene epoxy copolymer, that is, the final product poly 4-butyl 6-(4-((4-(ethoxycarbonyl)-phenyl)-azo)-phenyl) 2-(oxiran-2-ylmethyl) 2-methylheptane-2,4,6-tricarboxylate.

[0034] Among them, the synthetic route of azobenzene epoxy copolymer is as follows Figure 1 Then, the azobenzene epoxy copolymer is used to prepare an anti-ultraviolet material, wherein the original fiber product is treated with plasma to form hydroxyl groups on the surface, the treated fiber product is subjected to a ring-opening reaction with the epoxy groups in the azobenzene epoxy copolymer at high temperature to form ether bonds, the reacted fiber product is immersed in a nano-titanium dioxide dispersion, and is grafted on the surface of the treated fiber product at high temperature to finally obtain an anti-ultraviolet product.

[0035] In addition, the obtained azobenzene epoxy copolymer was subjected to nuclear magnetic resonance analysis (NMR instrument, WNMR-I-400MHz, Wuhan Zhongke Oxford Spectroscopy Technology Co., Ltd.) and infrared spectroscopy analysis (Fourier transform infrared spectrometer, Nicolet iS 10, ThermoFisher), and the results are as follows: Figure 4-5 shown.

[0036] From the signals in the nuclear magnetic resonance image, it can be seen that the structure of the target synthetic compound corresponds one-to-one with the peaks in the 1HNMR spectrum, so it can be determined that the synthetic product is the target synthetic compound 1-ADPAH; and the peak signal in the Fourier infrared spectrum can prove that the product is the target compound.

[0037] Application Example 1 On the basis of Example 4, this application example uses the azobenzene epoxy copolymer obtained in Example 4 for anti-ultraviolet finishing of PBO fiber, specifically including: (1) The PBO fiber to be treated was immersed in a mixed solvent of acetone and petroleum ether (volume ratio 2:1) for 12 h; after immersion, it was taken out and washed with anhydrous ethanol and deionized water to remove the sizing agent, and then dried in an oven at 80 °C for 24 h; The bath ratio between the PBO fiber to be treated and the mixed solvent is 1:30; (2) The dried PBO fiber is then fixed on a glass frame and surface activated using a low-temperature plasma treatment device to obtain modified PBO fiber; The plasma process parameters were set as follows: discharge power 120 W, discharge time 360 ​​s, oxygen flow rate 30 sccm; (3) Add appropriate amount of nano-titanium dioxide and ethylene dichloride into a beaker, perform ultrasonic treatment for 2 hours, and then dissolve the prepared azobenzene epoxy copolymer in the solution. The nano-titanium dioxide is wrapped by the azobenzene epoxy copolymer in the solvent (the mass of the nano-titanium dioxide is 0.5% of the mass of the solution), and obtain a reaction solution; The modified PBO fiber was immersed in the above solution for 1 hour, then taken out and placed in a 180°C oven for reaction for 0.5 hour, and the temperature was raised to 200°C for further reaction for 0.5 hour; The bath ratio between the modified PBO fiber and the reaction solution is 1:30.

[0038] The process of anti-ultraviolet finishing of PBO fiber by azobenzene epoxy copolymer is as follows: Figure 6 shown.

[0039] First, the structure of PBO fibers before and after treatment was characterized by electron scanning (scanning electron microscope, Phenom Pro, Phenom World), X-ray spectroscopy (Thermo Scientific K-Alpha) and Fourier transform infrared spectroscopy (Nicolet iS 10, ThermoFisher); The results are as follows Figure 7-9 As shown, the characterization results show that the copolymer was successfully grafted onto the PBO fiber.

[0040] 2. Testing the Anti-UV Performance of the Anti-UV PBO The results are as follows Figure 10-13 As shown in the figure, the results show that the tensile strength of the original PBO fiber dropped sharply after UV irradiation. After 288 hours of UV irradiation, the tensile strength of the single fiber dropped to 1.47 GPa and the tensile strength retention rate was only 28.2%; while the copolymer-modified PBO has excellent UV resistance; the tensile strength and retention rate after 288 hours of UV aging are 2.63 GPa and 49.8% respectively; In order to further improve the UV resistance, nano-titanium dioxide was combined on the basis of the copolymer. The tensile strength and retention rate of the sample after 288 hours of UV aging were 3.92 GPa and 73.7%, respectively.

[0041] Furthermore, it was concluded that the PBO fiber treated with azobenzene epoxy copolymer has better UV resistance and aging resistance, and effectively increases the service life of related fiber products.

[0042] Application Example 2 On the basis of Example 4, this application example uses the azobenzene epoxy copolymer obtained in Example 4 for anti-ultraviolet finishing of ramie fiber, wherein hydroxyl groups exist on the surface of ramie fiber itself, and form ether bonds by ring-opening reaction with epoxy groups in the azobenzene epoxy copolymer at high temperature, and the ramie fiber after the reaction is immersed in nano-titanium dioxide dispersion, and grafted on the surface of ramie fiber at high temperature, and finally obtains anti-ultraviolet products. The steps include: (1) The ramie fiber was washed with anhydrous ethanol and deionized water to remove the sizing agent, and then dried in an oven at 80°C for 24 hours; wherein the bath ratio of the ramie fiber to the washing liquid (anhydrous ethanol and deionized water) was 1:30; (2) Add appropriate amount of nano-titanium dioxide and dichloroethane into a beaker and perform ultrasonic treatment for 2 hours. Then, dissolve the prepared polymer in the solution, and the nano-titanium dioxide is wrapped by the polymer in the solvent (the mass of the nano-titanium dioxide is 0.5% of the mass of the solution), to obtain a reaction solution. (3) After soaking the ramie fiber in the above solution for 1 hour, take it out and put it into a 180°C oven to react for 0.5 hour, increase the temperature to 200°C and continue to react for 0.5 hour; wherein, the bath ratio of ramie fiber to reaction solution is 1:30.

[0043] The above description is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Any modification, equivalent substitution and inclusion made by any technician familiar with the technical field within the technical scope disclosed by the present invention and within the spirit and principle of the present invention should be covered by the protection scope of the present invention.

Claims

1. An azobenzene epoxy copolymer, characterized in that: The obtained product is prepared by using an azobenzene compound containing an olefin bond and an epoxy resin containing an olefin bond as raw materials under the action of a chain softener; The chemical structural formula of the azobenzene epoxy copolymer is as follows: ; Among them, x:y:z=2~3:1~2:2~3.

2. The azobenzene epoxy copolymer according to claim 1, characterized in that The chemical structural formula of the azobenzene compound containing an olefin bond is as follows: ; Among them, R1 represents alcohol, and R2 represents alkyl, hydroxyl, carboxyl or ester group.

3. The azobenzene epoxy copolymer according to claim 1, characterized in that The chemical structural formula of the epoxy resin containing olefin bonds is as follows: ; Wherein, R3 represents an alkyl group.

4. The azobenzene epoxy copolymer according to claim 1, characterized in that: The chemical structural formula of the chain softener is as follows: ; Wherein, R4 represents an alkyl group.

5. A method for preparing an azobenzene epoxy copolymer, characterized in that: The steps include: The azobenzene compound containing an olefin bond, the epoxy resin containing an olefin bond and the softening agent are dissolved in solvent I in a molar ratio of 1 to 3:1 to 3:1, and a catalyst with a mass fraction of 2 to 5% is added to react; after the reaction is completed, the reaction is dried to obtain an azobenzene epoxy copolymer.

6. The method for preparing the azobenzene epoxy copolymer according to claim 5, characterized in that: The reaction is refluxed at 75-85° C. for 4-6 hours. Preferably, the solvent I is tetrahydrofuran, methanol or ethanol; preferably, the catalyst is azobisisobutyronitrile, azobisisoheptanenitrile or diphenylmethyl peroxide.

7. The azobenzene epoxy copolymer according to any one of claims 1 to 4, or the azobenzene epoxy copolymer prepared by the preparation method according to any one of claims 5 to 6, is used to prepare an anti-ultraviolet material.

8. A method for preparing an anti-ultraviolet material, characterized in that: The steps include: S1: soaking the fiber product in a pretreatment liquid and drying it to obtain a pretreatment material; S2: The pre-treated material is immersed in the anti-ultraviolet treatment liquid at a bath ratio of 1:20 to 100, and the pre-treated material is placed in an oven for high-temperature treatment, washing, and drying to obtain an anti-ultraviolet finishing material; The method for preparing the anti-ultraviolet treatment liquid comprises: dissolving the azobenzene epoxy copolymer described in any one of claims 1 to 4, or the azobenzene epoxy copolymer prepared by the preparation method described in any one of claims 5 to 6, in a solvent II; preferably, the solvent II is ethylene dichloride, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide; S3: Immersing the anti-ultraviolet finishing material in a solution containing nano-titanium dioxide, loading, washing, and drying at a temperature of 180-200° C. to obtain the anti-ultraviolet material.

9. The method for preparing the anti-ultraviolet material according to claim 8, characterized in that: The preparation method of the pretreatment liquid comprises: mixing acetone and petroleum ether at a volume ratio of 1 to 3:1 to obtain a mixed solvent; and mixing the mixed solvent with anhydrous ethanol to obtain the pretreatment liquid.

10. The method for preparing the anti-ultraviolet material according to claim 8, characterized in that: The preparation method of the solution containing nano titanium dioxide comprises: adding 0.4-0.6% by mass of nano titanium dioxide into solvent II and performing ultrasonic dispersion to obtain the solution; preferably, solvent II is ethylene dichloride, N,N-dimethylacetamide, N,N-dimethylformamide or dimethyl sulfoxide.

Citation Information

Patent Citations

  • Preparation method of anti-ultraviolet textile fabric

    CN112030255A